Tariff approach to regulation of the European gas transportation system: Case of Nord Stream - Vadim Fetisov (Elsevier, 2021)
Nord Stream 2 is one of the most discussed energy projects, which affects the economic and political interests of many countries, not only the direct participants. Despite some uncertainty, the project is highly likely to be completed. In this regard, it is important to understand what impact it will have on the European gas market. This article proposes a simulation model for calculating the total cost of construction of the Nord Stream 2 and determines the cost of natural gas. It was concluded that Nord Stream 2 has an economic advantage overliquified natural gas (LNG) delivery schemes, a strategic value for the economies of the EU countries and will ensure the stability of gas supply, which is undoubtedly a priority for European energy policy.